BATIK EXTRACULICULAR AS A MEANS OF PLANTING VALUES OF CULTURE - Pangestu Cahyo Gumelar (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Abstract: Schools are part of the community, therefore schools must be able to strive for the preservation of the cultural richness of the community. Giriloyo Village, Imogiri, Bantul as an area that still preserves batik activities, and even batik becomes the main livelihood for several families. To continue to maintain this cultural heritage, MI Ma'arif Giriloyo I included batik extracurricular into local content that must be taken by students. This extracurricular batik aims to instill cultural values ​​so that students can foster a sense of love for their own culture. This type of research is qualitative research. Data collection techniques using the method of observation, documentation, and interviews. The object of this research is the implementation of batik extracurricular activities. With the subject of the Madrasah Head, Batik Extracurricular Teachers, students in grade V. Data analysis methods developed by Miles and Huberman are data reduction, data display, and conclusion drawing/verification. Test the validity of the data using reference material. The results of this study indicate that: 1) The batik extracurricular implementation is carried out consistently and systematically according to the learning steps starting from the introduction, core and closing activities. 2) The teacher develops the creativity of students by giving them freedom of expression and constant practice. 3) The inhibiting factors in batik extracurricular implementation are the lack of class hours, the amount of equipment that is not balanced with students, there is no specific place for batik practice. Factors supporting the implementation of batik extracurricular include the community environment, high student interest.